Performance measurement and incentive plans - Antti Kauhanen; Sami Napari (The Research Institute of the Finnish Economy (ETLA), 2010)
This paper explores performance measurement in incentive plans. Based on theory, we argue that differences in the nature of jobs between blue- and white-collar employees lead to differences in incentive systems. We find that performance measurement for white-collar workers is broader in terms of the performance measures, the organizational level of performance measurement and the time horizon. The intensity of incentives is also stronger for white-collar employees. All of these findings are consistent with theory.
Keywords: J33; M52; M54; 330; Incentive pay; performance measurement; risk versus distortion trade-off; agency theory; Leistungsorientierte Vergütung; Performance-Messung; Angestellte; Prinzipal-Agent-Theorie